Neuro-nutraceuticals: Insights of experimental evidences and molecular mechanism in neurodegenerative disorders - Pranay Wal; Namra Aziz; Biswajit Dash; Sachin Tyagi; Yadav Rupali Vinod (SpringerOpen, 2023)
Abstract Background One of the most important healthcare challenges in the world today is neurological disorders. Pose lifestyle changes are linked to a significantly higher risk of chronic illnesses and diseases, placing a significant financial and healthcare burden on society at large. In this review article, we focused on the various neuro-nutraceutical herbs and their beneficial roles in neurodegenerative disorders. Main body of the abstract An extensive literature review was done from the standard databases such as Scopus, Elsevier, and PubMed using standard keywords "Nutraceuticals", "Neuro-nutraceuticals", "Neurodegenerative disorders". Numerous "neuro-nutraceuticals" are natural plant compounds with dietary and pharmaceutical components that are intended to improve cerebral blood flow along with illness prevention and control. These compounds are found in food, herbal medicines, and nutritional supplements such as Bacopa monnieri, Curcuma longa, Asparagus racemosus, Helicteres angustifolia, Hericium erinaceus, Crocus sativus, Uncaria tomentosa, Centella asiatica, Convolvulus pluricaulis, Moringa oleifera. Short conclusion While discussing the neuroprotective and the neuromodulatory properties of various neuro-nutraceuticals, we rationally postulate here their molecular mechanisms. Additionally, compared to single-target medicines, which may have unfavourable side effects, these herbs are believed to be safer and to provide a more holistic improvement in brain health. Graphical Abstract